Czech Republic : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This Selected Issues paper on the Czech Republic discusses issues relating to the enterprise sector and corporate governance. This includes an overview and assessment of enterprise performance along with a discussion of the concept of corporate governance and its application in the Czech Republic, including how corporate governance practices compare in an international context. The paper discusses issues related to financial sector performance and restructuring. It also takes stock of banking sector developments and performance and reviews financial policy and supervisory challenges, including the definition of policies for bank privatization and the appropriate prudential framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet